FORMATION OF LEGAL CULTURE OF BUSINESS MANAGEMENT EMPLOYEES - Fakhritdinovich , Khatamov Farkhod (International Journal of Psychosocial Rehabilitation, 2020)
This article highlights the activities of business administration employees and the philosophical essence of their legal culture. It sets out the aspects of improving the legal culture of personnel in business management. Furthermore, it covers the role of society and the state in the formation of a legal culture in business management as well as it highlights the works that implemented to improve the business administration staff’s legal culture.